PENGARUHi TINGKAT SUKU BUNGA KREDIT, CAPITAL ADEQUACY RATIO DAN LOAN TO DEPOSIT RATIO TERHADAP NON PERFORMING LOAN PADA BANK PERKREDITAN RAKYATi DIiKOTA BATAM - Fitri, Aidinai; Efriyenti, Diani (LPPM Universitas Putera Batam, 2019)
Theipurposeiofithisistudyiwasitoi determine the effect of credit interest rates (X1), capital adequacy ratio (X2) and loan to deposit ratio (X3) on non-performing loans (Y) in rural credit banks in Batam city using SPSS 220. Data collection in this study uses secondary data in the form of income statementi and balance sheet from 2011 to 2015 using 60 samples from several credit banks in Batam City. Theianalysisi of this study using multiple linear regression analysis of the resultsi of this study showsithatithe loan interest rate does not significantly influence the non-performing loan, the capitaliadequacy ratio has a significant effect, the ratio of loan to deposit ratio has ai significant effect. simultaneously the loan interest rate, significant effect on non-performing loans.